DEVELOPMENT AND VALIDATION OF UV SPECTROPHOTOMETRIC METHOD FOR THE QUANTIFICATION OF METRONIDAZOLE IN PURE AND TABLET DOSAGE FORM - MUJITAPHA F.M.; USMAN, M.A.; YAKASAI, I.A. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Three simple, rapid and accurate spectrophotometric methods were developed for quantification of metronidazole in pure and tablet dosage form. The methods involved measurement of absorbance at wavelengths 295, 345 and 350 nm for pH 1.2, 4.5 and 6.8 respectively. The methods were validated according to ICH guidelines with respect to different analytical parameters; linearity, precision, accuracy and percentage recovery, Limit of detection (LOD) and Limit of quantification (LOQ). Beer-Lambert’s law was obeyed within the concentration range of 2- 64μg/mL. The Limit of detection and quantification values were determined to be 0.0122 and 1.1154, 0.0185 and 1.6935, 0.0858 and 0.26026 for pH 1.2, 4.5, and 6.8 respectively. The proposed methods were found to be precise since coefficient of variation (% RSD) values were less than 15 % and recovery values were found to be in the range of 95.71-100.71 %. The developed methods were successfully used for in-vitro dissolution of Metronidazole.